2022
DOI: 10.18502/ijps.v18i1.11408
|View full text |Cite
|
Sign up to set email alerts
|

Academic Procrastination, Depressive Symptoms and Suicidal Ideation in University Students: A look during the Pandemic

Abstract: Objective: The aim is to determine the relationship between academic procrastination, depressive symptoms and suicidal ideation in students of the Faculty of Health Sciences. Method: It was a non-experimental and cross-sectional study of correlational scope. The non-probabilistic convenience sample, made up of 578 participants between 16 and 30 years old (69% female), completed the Academic Procrastination Scale, the Positive and Negative Suicidal Ideation Inventory (PANSI) and the Beck Depression Invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Although procrastination is not a formal symptom of depression, it is a behavior often experienced by people living with depression [ 46 , 53 , 54 , 55 , 56 ]. Research has shown that procrastination is associated with various mental health challenges, including depression, anxiety, stress, and low self-esteem [ 44 , 45 , 46 , 47 , 48 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although procrastination is not a formal symptom of depression, it is a behavior often experienced by people living with depression [ 46 , 53 , 54 , 55 , 56 ]. Research has shown that procrastination is associated with various mental health challenges, including depression, anxiety, stress, and low self-esteem [ 44 , 45 , 46 , 47 , 48 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another negative consequence of mental health is increased levels of anxiety and depression symptoms [ 46 , 53 , 54 , 55 ]. Higher levels of academic procrastination were positively related to depression and suicide ideation among college students during the COVID-19 pandemic [ 56 ]. Procrastination is related to social media use, as suggested in a recent study [ 21 , 49 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning algorithms and data mining techniques are commonly utilized in student performance prediction modeling [2]. These techniques analyze various attributes such as grades, educational background, psychological evaluation, and demographics to generate predictions about a student's future performance [3]. By utilizing machine learning techniques, educators can gain valuable insights into student behavior and patterns, allowing them to tailor their approach to meet individual students' needs.…”
Section: Introductionmentioning
confidence: 99%
“…As academic procrastination increases, students' achievement (Lakshminarayan et al, 2013;Madhan et al, 2012), life satisfaction (Özer & Saçkes, 2011) and well-being (Arifiana et al, 2020) decrease, and depression (Cjuno et al, 2023;Yang et al, 2022), anxiety (Lima-Silva et al, 2022) and stress levels increase (Ashraf et al, 2019). In academic procrastination, the fact that the individual constantly leaves the tasks to the last minute and postpones them may cause problems in time management and may not be able to deliver the planned tasks on time.…”
Section: Introductionmentioning
confidence: 99%